SPATIAL DISTRIBUTION OF VIOLENCE AGAINST OLDER ADULTS BEFORE AND DURING THE COVID-19 PANDEMIC - Costa, Aline Balandis; Marques, Francielle Renata Danielli Martins; Oliveira, Natan Nascimento de; Oliveira, Rosana Rosseto de; Salci, Maria Aparecida; Facchini, Luiz Augusto; Carreira, Lígia (Cogitare Enfermagem, 2023)
Objective: to analyze the spatial distribution of violence against older adults in the Brazilian South region before and in the first year of the COVID-19 pandemic. Method: an ecological study that analyzed reports of violence against older adults between 2019 and 2020, in Southern Brazil. Local empirical Bayesian rates, Moran's Local Autocorrelation Index and Getis Ord Gi analysis were calculated. Results: there was a reduction in the smoothed rate of violence against older adults. The high-high and hot-spot cities in 2019 became more violent in 2020; and cities with low prevalence became less violent in 2020. The highest COVID-19 fatality rates were also in those cities with the highest violence rates. Conclusion: the data reinforces the complexity of violence and its worsening due to the pandemic. In addition, they contribute to decision-making in Nursing, highlighting the need to encourage new research studies on this theme.